2013
DOI: 10.2224/sbp.2013.41.8.1319
|View full text |Cite
|
Sign up to set email alerts
|

Blog user satisfaction: Gender differences in preferences and perception of visual design

Abstract: The World Wide Web is now used by all generations and classes. In addition to fulfilling the Internet's broad purposes in society, interface designers increasingly recognize the importance of visual aesthetics and end-user preferences in improving user satisfaction. We investigated gender differences in blog user satisfaction. Participants were 268 undergraduate students. The results revealed no statistical difference according to gender in how information quality and navigation quality influenced the satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Gender affects how individuals view the world, including the Internet (Cho and Hong 2013;Moss and Gunn 2009). Quality, up-to-date consumer health information can improve health outcomes for all genders (Lustria, Smith, and Hinnant 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Gender affects how individuals view the world, including the Internet (Cho and Hong 2013;Moss and Gunn 2009). Quality, up-to-date consumer health information can improve health outcomes for all genders (Lustria, Smith, and Hinnant 2011).…”
Section: Introductionmentioning
confidence: 99%
“…DeLone and McLean (1992) presented a user satisfaction model based on the notion that the quality of the system such as information and technical quality affects user satisfaction. Findings concerning the effect of the quality of attributes of a system on user satisfaction can be applied to maximize system value by considering these from the user's perspective (Cho & Hong, 2013).…”
Section: User Satisfactionmentioning
confidence: 99%
“…It was also possible that male students did not pay sufficient attention to visual information when it was given along with text. Cho and Hong (2013) found that women were more likely to consider visual design quality as an important factor to determine their satisfaction with a blog. In addition, women were more influenced by colour aesthetics than men, whereas men were more influenced by layout aesthetics in judging the visual design quality of a blog.…”
Section: Introductionmentioning
confidence: 99%